RIZ1 and histone methylation status in pituitary adenomas - Yake Xue; Ruokun Chen; Wei Du; Fengdong Yang; Xinting Wei (Tumor Biology, 2017)
RIZ1 displays strong tumor-suppressive activities, which has a potential histone methyltransferase activity. The objective of the study was to evaluate the level and the methylation status of RIZ1 and analyze its association with clinicopathological features and the histone in the pituitary adenomas. We found that RIZ1-positive cases were 11/50 and H-Scores 22.75 ± 11.83 in invasive pituitary adenomas and 26/53 and 66.3 ± 21.7 in non-invasive pituitary adenomas (χ 2  = 8.182, p = 0.004). RIZ1 and C-myc showed the opposite trend in these cases. The methylation levels of RIZ1 were more than 50% in 30.4% (7/23) CpG sites through MALDI-TOF Mass array. There was significant difference (p < 0.01) in 4 CpG sites between invasive pituitary adenoma group and non-invasive pituitary adenoma group; furthermore, the relieved methylation levels of H3K4/H3K9 and enhanced methylation levels of H3K27 in the patients’ serum were found. Furthermore, there was statistic difference of H3K4 and H3K27 methylation between invasive pituitary adenoma and non-invasive pituitary adenoma group (p < 0.01). The average progression-free survival in high RIZ1 group was 52.63 ± 7.62 months and 26.06 ± 4.23 months in low RIZ1 group (p < 0.05). Promoter region methylation of RIZ1 may play an important role in the epigenetic silencing of RIZ1 expression in pituitary adenomas, which may translate into important diagnostic and therapeutic applications.